Pdynmc - An R-package for estimating linear dynamic panel data models based on linear and nonlinear moment conditions - Markus Fritsch; Andrew Adrian Yu Pua; Joachim Schnurbus (Universität Passau, Wirtschaftswissenschaftliche Fakultät, 2019)
pdynmc is an R-package for GMM estimation of linear dynamic panel data models that are based on linear and nonlinear moment conditions as proposed by Anderson and Hsiao (1982), Holtz-Eakin, Newey, and Rosen (1988), Arellano and Bover (1995), and Ahn and Schmidt (1995). This paper describes the functionality of the package and the options regarding instrument type, estimation methodology, general configuration, specification testing and inference from the perspective of an applied statistician. The description of the functionality is based on replicating the results on a publicly available panel data set. Additionally, we link our implementation to other software and packages for GMM estimation of linear dynamic panel data models.
Keywords: C23; C87; 650; panel data; linear dynamic model; generalized method of moments; linear moment conditions; nonlinear moment conditions; R